Effect of Profitability, Liquidity, Foreign Ownership and Financial Distress on Tax Avoidance of Transportation & Logistics Companies - Margaretha, Fellycia; Jusuf, A An Arief (Formosa Journal of Applied Sciences, 2024)
Tax is a mandatory contribution owed by personal and corporate taxpayers and is one of the largest revenues for the state for the greatest prosperity of the people. But in reality, taxpayers often make tax avoidance efforts to minimize the tax payable. This study aims to examine the effect of Profitability, Liquidity, Foreign Ownership and Financial Distress on Tax Avoidance of transportation & logistics companies listed on the Indonesia Stock Exchange (IDX) in 2019 - 2023. This study uses secondary data and applies purposive sampling method, resulting in 50 companies being sampled based on certain criteria. The data analysis technique uses multiple linear regression analysis, with the help of IBM SPSS Statistics 25 software. The research findings reveal that the variables of Profitability, Liquidity and Financial Distress significantly affect Tax Avoidance. Although the Foreign Ownership variable does not affect Tax Avoidance.